7 - Reflections on an Innovative Mentoring Partnership Facilitators and Inhibitors to Success in Faculty Development - Chapman, Marilyn; Khamis, Tashmin (Journal of Higher Education in Africa, 2022)
The need for more interactive, learner-centred pedagogies at Aga Khan University in East Africa led to the development of a partnership with Academics without Borders (AWB). AWB recruited three nursing faculty volunteers to provide mentorship to the nursing faculty at the three Aga Khan University Advanced Nursing Studies campuses in East Africa. As part of the evaluation and as a strategy to improve the quality of the mentoring and the project, the authors developed an action research study to identify facilitators and inhibitors to the success of this inter-cultural initiative. In this article, the authors share their observations and reflections as recorded in journal entries and postings to an online site as well as the results of a strengths, weaknesses, opportunities and threats (SWOT) analysis completed by mentees, mentors and project coordinators. Finally, the authors share their thoughts on the implications for future cross-cultural mentoring relationships at Aga Khan University and the potential for assisting others in similar relationships.